Creative Housing Design: Promoting sustainable living in cohousing community in the UK - Wang, Jingjing; Pan, Yiru; Hadjri, Karim (Environment-Behaviour Proceedings Journal, 2018)
A cohousing community is created and managed by its residents. It is a new collaborative housing concept designed to foster meaningful relationships, closer social bonding and energy efficiency concepts. This paper aims to discuss the key principles, priorities and challenges of cohousing design process through interviews with four cohousing project architects and four members of the design group. Semi-structured interviews were carried out i) to understand residents’ thinking and behaviour change through living in the cohousing community, and ii) to establish the environmental and social sustainability in a cohousing setting. The study found that the development procedure of cohousing highly differs from the mainstream housing design. The quality of the design can potentially influence the residents’ daily life. The findings will benefit a range of groups. It will be an important reference for cohousing design standards. Also, it could potentially become the legitimate toolkit for cohousing groups.